Antibodies to SARS-CoV-2-related linear epitopes induce neuroinflammation of mice - XU Jinming, HONG Yuxuan, WEI Hui, XU Qi (Jichu yixue yu linchuang, 2023)
Objective To evaluate the potential biological functions of non-viral neutralizing antibodies associated with linear epitopes of the SARS-CoV-2 spike protein. Methods The linear epitope S2-78 with the highest response frequency and longest antibody retention time in COVID-19 patients was selected according to previous reports. After immunizing mice with keyhole limpet hemocyain conjugated S2-78 polypeptide(KLH-S2-78), the serum anti-S2-78 IgG antibody level, mouse behavioral phenotype and the density of microglia in the brain were detected. Results KLH-S2-78 immunized mice developed high titers of anti-S2-78 IgG antibodies(the highest titer was 25 600, A450=0.305 5), a psychomotor-like behavioral phenotype with defective sensorimotor gating, impaired olfactory function, and impaired spontaneity. The density of microglia significantly increased in the cortex and hippocampus(P＜0 .05), suggesting a state of central inflammatory stress. Conclusions Anti-S2-78 IgG antibody may cause neuroinflammatory damages in the brain tissue by stimulating the host inflammatory response.